2021
DOI: 10.1371/journal.pone.0250462
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes self-care practice and associated factors among type 2 diabetic patients in public hospitals of Tigray regional state, Ethiopia: A multicenter study

Abstract: Background The prevalence of type 2 diabetes is increasing steadily at an alarming rate. Ethiopia is placed fourth among the top five countries of the African region members of the international diabetes federation. This study aimed to determine the level of diabetes self-care practice and associated factors among patients with type 2 diabetes mellitus attending public hospitals of the Tigray region. Methods An institution-based, cross-sectional study was conducted in six selected hospitals of Tigray region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 25 publications
4
28
4
1
Order By: Relevance
“…This finding was in line with the study conducted in central Tigray hospital 62.7% [27], and west Ethiopia at 57.3% [28]. However, this finding was higher than a study conducted at Debre Tabor University 36.9% [29], in Addis Ababa Ethiopia 52% [30], Jimma medical center 45.8% [31], in Tigray 53.3% [19]. The possible reasons could be the…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This finding was in line with the study conducted in central Tigray hospital 62.7% [27], and west Ethiopia at 57.3% [28]. However, this finding was higher than a study conducted at Debre Tabor University 36.9% [29], in Addis Ababa Ethiopia 52% [30], Jimma medical center 45.8% [31], in Tigray 53.3% [19]. The possible reasons could be the…”
Section: Discussionsupporting
confidence: 88%
“…This finding was in line with the study conducted in central Tigray hospital 62.7% [ 27 ], and west Ethiopia at 57.3% [ 28 ]. However, this finding was higher than a study conducted at Debre Tabor University 36.9% [ 29 ], in Addis Ababa Ethiopia 52% [ 30 ], Jimma medical center 45.8% [ 31 ], in Tigray 53.3% [ 19 ]. The possible reasons could be the difference in socio-cultural variation, lifestyle, and inadequate access to glucose monitoring machines, test strips, and levels of education in the patients were differences in self-care practice.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Previous studies conducted in Ethiopia showed that the overall prevalence of good diabetes self-care behavior varied widely among diabetic patients ranging from 28.4-76.8% [14][15][16]. This wide variation in self-care practice is expected for a multinational country like Ethiopia that has socioeconomic and cultural varieties.…”
Section: Introductionmentioning
confidence: 99%
“…It results from a defect in insulin secretion, defective insulin action, or both, which leads over time to serious damage to different organs [1 ].According to the international diabetics Federation (IDF) Diabetes Atlas 2019, there are an estimated 463 million(9.3%) people with diabetes aged from 18-79, and the number of people to rise beyond 700 million in less than 25 years worldwide if not controlled. Of these people, 19.4 million adults live in Africa and Ethiopia is one of the members of IDF with 1.7 million people with diabetes [2,3].…”
Section: Introductionmentioning
confidence: 99%